Pengaruh Biaya Lama Melaut dan Harga Terhadap Pendapatan Nelayan Alor - Junius Menase Sabu; Maryanti Sofyan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study was to determine the effect of cost, duration of fishing and selling price on fishermen's income. The analysis technique is descriptive analysis. The population in this study is the entire fishing community in Adang Village, Alor Regency. The sampling method is accidental sampling. This study uses primary data and the statistical method in this study is multiple linear regression. This type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This study uses primary data and the statistical method used in this study is multiple linear regression with a significant t test and a significant f test as a benchmark for taking hypotheses and the results of data management using the IBM Spss 22 For Windows program. The results of this study indicate that: (1) partially the cost has an effect on income with a significance value of 0.035 or 3.5% so that the results of this study accept H1, (2) partially the length of time at sea has an effect on income with a significance value of 0.000 or 0. .0%, so the results of this study accept H2, (3) partially the price has an effect on income with a significance value of 0.000 or 0.0%, so that the results of this study accept H3, (4) simultaneously costs, length of time at sea, and price has an effect on income with a significance value of 0.000 or 0.0%, so the results of this study accept H4.